Penyuluhan dan Praktek Budidaya Jamur Tiram bagi Karang Taruna Desa Codo Kab. Malang - Maria Intan Kumala; Tikka Dessy Harsanti; Onyka Abdillah (Dedikasi Cendekia: Warta Pengabdian Pendidikan, 2024)
Real Work Lectures (KKN) are one of the courses programmed for UM students. These courses include field practice courses which aim to train and equip students to apply their knowledge and learn to solve various real problems that occur in society. Observation results show that mushroom farming is not widely practiced by the people of Codo village. The majority of people still cultivate conventional farming such as rice, palm crops and various other agricultural products. In implementing the KKN program in Codo Village, the program chosen was counseling and mushroom cultivation practices for youth organizations in Codo Village. The method for implementing this service activity is carried out through counseling steps: (1) observation; (2) planning; (3) make a schedule and make invitations; (4) contacting sources; (5) conducting outreach and practice for youth organizations at the Codo village hall; and (6) Giving several mushroom seeds to representatives of youth organizations. The results of the implementation of extension programs/activities and harvesting practices for mushroom cultivation for youth organizations in Codo village, Wajak sub-district, Malang Regency, have achieved 85% of the expected results. The program started with counseling given by speakers who were brought directly from Batu City, namely entrepreneurs. Many parties are willing to help and work together for the smooth running of this program.